ANALISIS GAYA KEPEMIMPINAN KI HAJAR DEWANTARA, KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA DAN MOTIVASI GURU DI SMA MUHAMMADIYAH YOGYAKARTA - Cahyono Setia Wibowo (Universitas Sarjanawiyata Tamansiswa, 2022)
The study aims to determine the effect of leadership style on work motivation,influence of competence on teacher work motivation, influence of compensationon teacher work motivation, influence of leadership style, competence, andcompensation together on work motivation, influence of leadership style onteacher performance, influence of competency on teacher performance, the effectof compensation on teacher performance, and the effect of work motivation onthe performance of Muhammadiyah High School teachers in Yogyakarta.